Gene expression: chemical synthesis and molecular cloning of a bacteriophage T5 (T5P25) early promoter. - Rommens, J (1983)
A sixty base pair DNA duplex containing the nucleotide sequence of the bacteriophage T5 early (T5P25) promoter has been constructed using a combination of chemical synthesis and enzymatic methods. Subsequent to cloning into pBR322, the promoter has been demonstrated to be biologically active being capable of directing the efficient expression of genes under its control. This serves as a prototype for an approach to the study of the in vivo structure-function relationships and efficiency of promoters.